Eccentric exercise training in chronic mid-portion Achilles tendinopathy: A systematic review on different protocols - Habets, B.; van Cingel, R. E. H. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Although eccentric exercise training has shown favorable results in chronic mid-portion Achilles tendinopathy, the optimum dosage remains unknown. A systematic review of the literature was performed in accordance with the PRISMA guidelines, in order to describe different exercise protocols and to determine the most effective training parameters. An extensive search in MEDLINE, EMBASE, CINAHL, and CENTRAL revealed 14 randomized and clinical controlled trials. Strong evidence was found for the Alfredson exercise protocol. In this 12-week protocol, exercises are performed 3×15 repetitions twice daily, both with a straight and bent knee. Exercises are performed at slow speed, and load is increased when exercises are without pain. Strong evidence was also found for gradual onset of exercises during the first week of the Alfredson program, but no uniformity of protocols exists. Other exercise protocols did achieve similar results, but many studies had some methodological shortcomings or lacked a detailed description of their training parameters. Because of the heterogeneity of study populations and outcome measures, and lack of reporting of training compliance data, a definitive conclusion regarding the most effective training parameters could not be made. Further research comparing the content of different exercise protocols is warranted.